Persepsi dan Perilaku Orang Tua terhadap Sex Education Pada Anak Usia Dini - J, Jumiatun (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Sex education is very important to be given to early childhood (ages 0 - 6 years), as a provision for children to have a good self-concept when they are adults, aiming to provide knowledge, broaden children's horizons, and prevent children from various negative risks, such as sexual violence. Cases of violence recorded in the Online Information System for the Protection of Women and Children (SIMFONI - PPA) during the period from January 2023 to the present have been recorded at 20,099 cases, 57.3% of victims are children. The trend of violence against women and children in Kendal in 2023 is quite high, data from January-October recorded 120 cases, consisting of children in conflict with the law (ABH) as many as 49 cases (41%), violence against women as many as 26 cases (26%), and violence against children as many as 45 (38%). The role of parents is very important in preventing sexual violence against children by introducing sex education to early childhood. This study aims to determine parents' perceptions of sex education in early childhood. type of quantitative descriptive research. The instrument used in data collection was a questionnaire with a Likert-3 scale, statistical tests using chi square. The results of the study showed that the majority of respondents had negative perceptions (62.5%), good behavior of 75% and there was an influence between perception and parental behavior towards sex education in early childhood at KB Taruna Asih.